Thoughts of Prophet Muhammed Companions and Disciples - Dr. Akhlaque Ahmad (Jaipur, Keya International Press LLP, 2024)
The Quranic account of Moses is generally in accord with the biblical account. A major exception to this is one section in Surah 18. This section contains an extraordinary narrative of the prophet Moses and his mysterious travel companion. The Quran does not present any information on the identity of this bizarre individual. On areas not elaborated, Islamic traditions generally complement the Quran. In the case of this narrative, however, parallel canonical traditions provide tantalizingly few additional details. Traditional Muslim scholars and Muslim mystics or Sufis have made their own contributions in terms of providing a further exposition of this narrative. The narrative in question, in its diverse contexts, appears to have been a source of addressing the problem of the authority of Sufi .....